Saving India from Indira: the untold story of emergency - Goyal, Rama ed. (New Delhi Rupa, 2019)
Goyal was not merely witness to history but an active participant in its making. $1 (BArun Jaitley During the nearly seventy-two years since Independence, India has deviated from democratic life only once$1 (Bduring the twenty-one months of Indira Gandhi$1 (Bs Emergency. Saving India from Indira describes the events leading up to, and during the darkest days of, democratic India, as they actually unfolded. Recounted by J.P. Goyal, a key lawyer for Raj Narain in the famous election case against Mrs Gandhi that led to the imposition of the so-called National Emergency on 25 June 1975 at the behest of then prime minister Indira Gandhi, this no-holdsbarred account of a crucial insider describes the twists and turns in this case in the Allahabad High Court and the Supreme Court of India. It gives a blow-by-blow account of the battle that Goyal, along with a battery of lawyers, waged in the Supreme Court to defend the Constitution of India against the amendments that could alter its basic structure. This gripping narrative includes an account of Goyal$1 (Bs meetings with political leaders in jail, including Jayaprakash Narayan and Raj Narain, and reveals many hitherto unknown facts that Goyal was privy to. Saving India from Indira is a sharp memoir of one of those few who fought against the misdeeds of the dark era and recorded events for posterity.s
Keywords: History-India-During 1966-1977; National Emergency-India-Indira Gandhi